The development of cognitive empathy and concern in preschool children: A behavioral neuroscience investigation. Issue 3 (18th May 2017) - Decety, Jean; Meidenbauer, Kimberly L.; Cowell, Jason M.
Abstract: This developmental neuroscience study examined the electrophysiological responses (EEG and ERPs) associated with perspective taking and empathic concern in preschool children, as well as their relation to parental empathy dispositions and children's own prosocial behavior. Consistent with a body of previous studies using stimuli depicting somatic pain in both children and adults, larger early ( 200 ms) ERPs were identified when perceiving painful versus neutral stimuli. In the slow wave window ( 800 ms), a significant interaction of empathy condition and stimulus type was driven by a greater difference between painful and neutral images in the empathic concern condition. Across early development, children exhibited enhanced N2 to pain when engaging in empathic concern. Greater pain‐elicited N2 responses in the cognitive empathy condition also related to parent dispositional empathy. Children's own prosocial behavior was predicted by several individual differences in neural function, including larger early LPP responses during cognitive empathy and greater differentiation in late LPP and slow wave responses to empathic concern versus affective perspective taking. Left frontal activation (greater alpha suppression) while engaging in affective perspective taking was also related to higher levels of parent cognitive empathy. Together, this multilevel analysis demonstrates the important distinction between facets of empathy in children; the value of examining neurobehavioral processes in development. It provides provoking links between children's neural functioning and parental dispositions in early development. Abstract : Differences in children's frontal alpha asymmetry when perceiving others in distress is predicted both by chldren's empathy and their parents cognitive empathetic dispositions. Children electrophysiological measures show early and late distinctions in response to the suffering of others. Their prosocial behavior is predicted by neural marker of cognitive empathy. Their parents dispositional empathic concern positively predicts children's prosocial behavior.